Understanding security - Bourne, Mike, 1975- (Houndmills, Basingstoke : Palgrave Macmillan, 2014)
"This broad-ranging new text introduces a wide range of theoretical perspectives with a central focus on their application to understanding key issues in global, state and human security in the contemporary world."--Publisher's website.
Introduction: What is Security? -- Understanding and Theorizing security -- Traditional rationalist approaches to security -- Critical approaches and new frameworks -- The Sovereign state and internal security -- Acting under uncertainty: the security dilemma, strategy and risk -- Global and regional security formations -- War and killing -- Arms trade, arms control and disarmament -- Human security -- Weak states and intervention -- Terrorism and Counterterrorism -- Migration, crime and borders -- Environmental, energy and resource security -- Conclusion.
economic&political bookfair2015
Includes bibliographical references (pages 308-339) and index.
Keywords: Security, International; Human security